Levels of Conceptualization and Municipal Politics: Replication in a New Context - Matthews, J. Scott; McGregor, R. Michael; Stephenson, Laura B. (Frontiers in Political Science, 2021)
Since Angus Campbell and colleagues introduced the Levels of Conceptualization (LoC) framework as a measure of political sophistication, only a very small number of scholars have applied this approach to understanding how electors view political actors. In 2008, Michael Lewis-Beck and colleagues replicated this foundational study and found similar results using much more recent data on American national elections. In this brief research report, we replicate the work of Lewis-Beck and colleagues in the Canadian municipal context. Using survey data from the Canadian Municipal Election Study, we make use of open-ended responses about attitudes towards mayoral candidates to conduct a qualitative examination of the manner in which survey respondents from eight Canadian cities view mayoral candidates. Despite the relative dearth of ideological cues at the local level, we nevertheless find that a noteworthy portion of the electorate views candidates in ideological terms. Like previous work on the subject, we find that high levels of conceptualization are positively associated with turnout, education, political knowledge, and ‘political involvement’.